Ergonomics Simulation for Schoolchildren Using Virtual Reality (VRGo) - Nazarudin, Ain Najwa (IRC, 2019)
VRGo is a virtual reality (VR) application developed to serve as a platform to gain awareness among students in relation to schoolchildren ergonomics. In this work, schoolchildren ergonomics are referred as comfortable ways of sitting in classroom as well as the correct posture of carrying school backpack with the right weight. Poor ergonomics can lead to negative impact to health which is musculoskeletal pain. During class, student regularly sit with poor stance, having their trunk, back, and neck flexed or turned for long periods which can increase musculoskeletal pain from the classroom environment. Therefore, by trying to apply virtual environment in the learning process through VRGo application, this would as much grab the children interest about ergonomics and making them absorb the materials even more compared to the previous conventional ways of learning and training methods. It is surely will be interactive and fun to the school-aged children as Virtual Reality has 3D elements in it which can let them imagine it inside their head and be stored as memory. There are several objectives of this study which are to identify the suitable method in creating simulation in virtual reality, to develop schoolchildren ergonomics VRGo prototype application and also to conduct the test of functionality for VRGo. Survey and questionnaire based on Standard Nordic Body Map Questionnaire (SNBMQ) is done at a school in Kedah for 9 and 11 years old children to gather information of ergonomics among the students. Unity 3D and C# scripting along with Google Cardboard are used to develop the application.